Skin immune microenvironment in psoriasis: from bench to bedside - Yao, Yi; Chen, Li-Qing; Lv, Yi-Bo; Tang, Shun-Li; Shen, Wei; Sun, Hui; Zhong, Hua-Jie (Frontiers in Immunology, 2025)
Psoriasis, a chronic immune-mediated inflammatory skin disorder affecting approximately 2-3% of the global population, manifests in distinct forms including plaque, pustular, and erythrodermic types. The pathogenesis involves complex interactions between genetic susceptibility, epigenetic modifications, and environmental triggers that disrupt immune homeostasis, particularly within the skin’s epithelial immune microenvironment (EIME). This review examines the fundamental mechanisms of psoriasis from a ‘bench’ perspective, encompassing genetic triggers, immune cell contributions, cytokine cascades, and insights derived from multi-omics studies. It also incorporates emerging areas such as gut microbiota dysbiosis and neuro-immunological influences. Translational research linking these discoveries to clinical application is discussed, covering biomarker identification, comorbidity management, and the advancement of novel therapies. At the ‘bedside’, we evaluate current conventional treatments, targeted biologic agents (e.g., TNF-α, IL-17, and IL-23 inhibitors), and emerging modalities including JAK inhibitors, epigenetic modulators, and stem cell therapies. Challenges pertaining to efficacy, safety, and personalized medicine are addressed, alongside future directions emphasizing multi-omics integration and holistic immune targeting. Highlighting the critical role of the immune microenvironment, this narrative review underscores the translational progress driving towards improved patient outcomes.